The Influence of Job Stress on Turnover Intention in Gen Z - Inggartika, Rhaeditias; Khoiriah, Khoiriah; Aziza Putri, Fahma (International Journal of Social Science, Education, Communication and Economics, 2024)
This study aims to determine the effect of work stress on turnover in generation Z at Company X Jakarta. The variables studied in this study are work stress as an independent variable (X) and turnover intention as a dependent variable (Y). In this study, the approach used is quantitative. In research with a quantitative approach, the main objective of the researcher is to measure certain variables accurately. The type of sampling used in this study is accidental sampling, namely in taking research samples, researchers pay attention to certain criteria. This type of sampling is used because it considers practicality and availability of resources. The sample criteria in this study are Generation Z who have worked for at least 1-2 years in a company. The survey containing measuring instruments for the three variables was distributed online via social media. Based on the data obtained, there is a positive influence between the two factors, namely work stress and turnover intention. The higher the work stress, the higher the turnover intention of Generation Z, and vice versa, the lower the work stress, the lower the turnover intention with a value of = 0.791 with a p value = <.001 (p <0.05). This means that the higher the work stress, the higher the turnover intention of Generation Z, and vice versa, the lower the work stress, the lower the turnover intention.